Quality Control and Assurance - An Ancient Greek Term Re-Mastered 2017
DOI: 10.5772/66199
|View full text |Cite
|
Sign up to set email alerts
|

A Framework to Manage Quality of Enterprise Content Management Systems

Abstract: There is a wide range of enterprise content management ECM systems which supports, among other things, document management processes, records management and Web content management. However, each of these systems has many features and some of them can meet organizational needs depending on the scale, sector and worklow of the organization. In addition, it is very common that organizations are unaware of what ECM system best its their needs, since each company has its particular scope and strategic objectives. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…However, as the systems grow larger and more complex, the objectives and boundaries of ECM projects have become difficult for today’s companies to define, although doing so is essential to developing an ECM strategy and implementation plan. The solutions that have been offered under the umbrella of “ECM” differ considerably in terms of functionality, and the organizational needs they meet depend on the organizations’ sizes, businesses and structures, so it has become difficult for companies to identify the systems that best match their individual requirements (Enríquez et al , 2017). Organizations have diverse and often unique information management needs, so defining the boundaries and scopes of ECM projects is an important precondition for developing an ECM strategy and roadmap (Hullavarad et al , 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as the systems grow larger and more complex, the objectives and boundaries of ECM projects have become difficult for today’s companies to define, although doing so is essential to developing an ECM strategy and implementation plan. The solutions that have been offered under the umbrella of “ECM” differ considerably in terms of functionality, and the organizational needs they meet depend on the organizations’ sizes, businesses and structures, so it has become difficult for companies to identify the systems that best match their individual requirements (Enríquez et al , 2017). Organizations have diverse and often unique information management needs, so defining the boundaries and scopes of ECM projects is an important precondition for developing an ECM strategy and roadmap (Hullavarad et al , 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Alalwan and Weistroffer, 2012; Grahlmann et al , 2012; Rickenberg et al , 2012; Simons and vom Brocke, 2014). In proposing a variety of ECM definitions (Enríquez et al , 2017), researchers have found ECM to overlap with approaches like knowledge management, information resource management, document management, records management and (web) content management (e.g. Munkvold et al , 2006; Rickenberg et al , 2012; Svärd, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In consequence, this paper presents an independent study based on a rigorous and formal method, named QuEF, that has been successfully applied to other contexts [35,36]. Then, the main purpose of this paper is not only to achieve the best quality for PLM systems, but to encourage final users to make better decisions, as their choices will clearly depend on the context and enterprise needs (background, internal organization or relative importance given to each aspect by a particular enterprise).…”
Section: Discussionmentioning
confidence: 99%